INDEPENDENCE AND FINANCIAL EXPERTISE OF AUDIT COMMITTEE ON VOLUNTARY DISCLOSURE OF DEPOSIT MONEY BANKS IN NIGERIA - Saidu MUSA; Muhammed Kamaldeen Usman; Paul B. Ogunwole (Malete Journal of Accounting and Finance, 2023)
The recurrent collapse of financial institutions has engendered a lack of public confidence in the quality of financial and non-financial information disclosed by the management of listed Deposit Money Banks (DMB’s) in Nigeria. Voluntary disclosure practice especially in the Nigerian banking industry has been adjudged unsatisfactory and contributes to the lack of public confidence in financial information in Nigeria. Hence, this study investigates empirically the factors that influence the voluntary disclosure practices of listed Deposit Money Banks in Nigeria. The specific objectives of the study are to: investigate the magnitude to which audit committee composition affect voluntary disclosure practices of listed DMBs in Nigeri; and examine the extent to which audit committee independence influences voluntary disclosure practices of listed DMB’s in Nigeria using the Ex-post facto research design. Secondary data was employed to extract information from the annual reports of the twelve listed deposit money banks for eleven years, from 2008 to 2018., 2008 marked two years after the Central Bank of Nigeria CBN’s ₦25bn recapitalisation policy which made Nigerian banks more financially sound through mergers and acquisition. 2018 was also the latest year to which the annual reports of these banks were made available for public access. The information derived from the eleven years was statistically analysed using the Generalized Linear Regression. The result shows that audit committee composition does not significantly influence disclosure practices of listed DMBs in Nigeria (z=0.372, p>0.05) and audit committee independence constitutes a significant influence on the voluntary disclosure practice of listed DBMs in Nigeria (z=3.069, p-value < 0.01). The study therefore concludes that the presence of members with accounting and finance background on the audit committee does not influence the disclosure practice of listed DMBs as the inclusion of non- executive directors proved otherwise. The study therefore recommends that government and regulatory agencies should mandate the addition of accounting experts on the board of audit committees rather than the openness of financial expertise covering all fields of management stated in the Nigerian code of Corporate Governance (2016).